ANALISIS EFEKTIVITAS BIAYA PENGGUNAAN AMLODIPIN DIBANDINGKAN KAPTOPRIL PADA PASIEN HIPERTENSI DI RUMAH SAKIT UMUM DAERAH MAJENE PERIODE JANUARI HINGGA JUNI TAHUN 2019 - Andi Maulana Kamri; Rachmat Kosman; Dian Rahayu (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Hypertension is a chronic disease that requires long-term treatment and high cost. The research aimed to determine a more cost-effective treatment between amlodipine and captopril in hypertensive patients at Majene Hospital from January to June 2019. The sampling technique was purposive sampling with a cross-sectional method. The data collection was obtained from medical records and direct medical costs of hypertensive patients who take amlodipine or captopril. The Mann-Whitney statistical test was performed to determine the significant difference between the treatment groups. The results showed that the Average Cost Effectiveness Rasio (ACER) value of the 5 mg amlodipine and 12.5 mg captopril groups was Rp. 4233.3 and Rp. 4904 with an Incremental Cost Effectiveness rasio (ICER) value of Rp. 1063.5. Meanwhile, the Average Cost Effectiveness Rasio (ACER) value of the 10 mg amlodipine and 25 mg captopril group was Rp. 3764,7 and Rp. 4875.1. In conclusion, amlodipine is more cost effective than captopril.